Rating the rating agencies: Anticipating currency crises or debt crises? - Sy, Amadou N.R. (Journal of Banking & Finance, 2004)
We revisit the question whether sovereign ratings predict financial crises. In line with previous studies, we find that ratings do not predict currency crises and are instead downgraded ex-post. However, the likelihood of currency crisis and the implied probability of sovereign default are not closely linked in emerging markets post-1994. When debt crises are defined as sovereign distress – when spreads are higher than 1000 basis points or 10 percentage points – we find that access to international capital markets is reduced by half. In addition, although sovereign distress events last for typically 5.2 consecutive months, they can persist for longer periods up to nine quarters. Finally, lagged ratings and ratings changes, including negative outlooks and credit watches, are useful in anticipating sovereign distress.